THE INFLUENCE OF THE TEACHER’S QUESTIONING STRATEGIES ON THE ELEVENTH GRADE STUDENTS’ SPEAKING ACHIEVEMENT AT SMKN 1 PALEMBANG - ASWADI JAYA (Universitas Jambi, 2017)
Speaking ability is able to describe how far the language learner mastered about the language because it covers all of English elements. However, many students consider that speaking is not easy. The use of a variety of questioning strategies is recommended, focusing primarily on the higher end of Bloom’s taxonomy to engage students in advanced-level thinking. Teachers can incorporate questions effectively by knowing the various purposes, types, and intended outcomes and by establishing a classroom climate that promotes active engagement, exploration, and inquiry to further student achievement. Therefore, this study investigated whether or not teacher’s questioning strategies would influence the speaking achievement of the eleventh grade students at SMKN 1 Palembang . The problem of this study was “Do the teacher’s questioning strategies influence the eleventh grade students’ speaking achievement at SMKN 1 Palembang? In this study, the quasi-experimental method was used, data were taken from the result of the test, both the pre-test and post-test. The writer applied three techniques to analyze the data, first, the scoring rubric of speaking, second, the conversation of percentage range and, third, the matched t-test. The analysis of independent sample t-test showed that the mean difference of the post-test each group was 11.200 and the significant level was 0.000 since 0.000 was lower than alpha value 0.05, it meant that there was significant difference in speaking between two groups. This confirmed that the students in experimental group made better achievement it was compared to those of the students in control group. It could be meant that the use of teacher’s questioning strategies influenced the eleventh grade students’ speaking achievement at SMKN 1 Palembang.